"Equiheptatonic" Tuning in Thai Classical Music: Strict Propriety and Step Sizes. (7th January 2019) - Rahn, Jay
Tunings of Thai classical music have been a source of disagreement during the past century. Focusing on 28 ensembles, the present study analyzes ways in which the intervals they produce can be formulated so that they are both falsifiable and verifiable. Of these, a model that corresponds to Rothenberg's formulation of strict propriety excels among pairs of tones that span different numbers of scale degrees. According to Rothenberg's model of strict propriety, intervals that span fewer scale degrees are smaller than intervals that span more scale degrees. Further, according to a formulation of clear patterning among intervals that span precisely two scale degrees (i.e., a single step), there is no clear pattern of one-step intervals unless all the instances of at least one interval that spans two particular consecutive scale degrees are smaller and/or larger than all the instances of all the other intervals that span two consecutive scale degrees. Among the 28 ensembles, single-step intervals tend to constitute chains that overlap in size rather than a clear pattern of small and large intervals.